Vitamin D and curcumin-loaded PCL nanofibrous for engineering osteogenesis and immunomodulatory scaffold - Al-Bishari, Abdullrahman M.; Al-Shaaobi, Bilal A.; Al-Bishari, Aisha A.; Al-Baadani, Mohammed A.; Yu, Liang; Shen, Jiating; Cai, Lei; Shen, Yiding; Deng, Zhennan; Gao, Peng (Frontiers in Bioengineering and Biotechnology, 2022)
Successful rehabilitation of bone defects remains a major challenge in clinical orthopaedics, especially in the critical-sized. Nanofibers are achieving great attention in the biomedical field due to their biocompatibility, suitable size and mechanical properties. Herein, a guided bone regenerative scaffold was developed and loaded with vitamin D (Vit D) and curcumin (Cur) to enhance anti-inflammatory activity and osteogenesis ability by controlling these biomolecules' release. In vitro, the synergistic effect of these two biomolecules showed enhancement of the anti-inflammatory activity. Moreover, these biomolecules enhanced the osteogenic proliferation and differentiation of MC3T3-E1 by releasing from the scaffold that lasted up to 25 days. Furthermore, in vivo evaluation of bone regeneration using the target scaffolds to repair skull defects in rabbits was carried out. The findings confirmed that the defect area with Vit D/Cur-loaded scaffold was wholly filled with the newly formed bone after one month compared with other groups. These results indicate that the PCL scaffolds loaded with Vit D/Cur can be applied for potential bone regeneration therapy.